2016
DOI: 10.1128/jvi.02729-15
|View full text |Cite
|
Sign up to set email alerts
|

Functional Comparison of Molluscum Contagiosum Virus vFLIP MC159 with Murine Cytomegalovirus M36/vICA and M45/vIRA Proteins

Abstract: Molluscum contagiosum virus (MCV) gene IMPORTANCEMCV is a human-pathogenic poxvirus that cannot be propagated in cell culture or laboratory animals. Therefore, MCV gene products have been studied predominantly in cells expressing individual viral genes. In this study, we analyzed the function of the MCV gene MC159 by expressing it from a different virus and comparing its functions to those of two well-characterized MCMV genes. In this system, MC159 displayed some but not all of the previously described functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 54 publications
2
19
0
Order By: Relevance
“…NEMO was not immunoprecipitated under these conditions, showing the specificity of the immunoprecipitation conditions. MC159 was also coimmunoprecipitated with FLAG-NEMO, in agreement with data from previous reports (14,35). Thus, these results suggest that MC159 antagonized NEMO polyubiquitination, likely by interacting with NEMO, and warranted further study into how MC159 prevented NEMO polyubiquitination.…”
supporting
confidence: 90%
See 4 more Smart Citations
“…NEMO was not immunoprecipitated under these conditions, showing the specificity of the immunoprecipitation conditions. MC159 was also coimmunoprecipitated with FLAG-NEMO, in agreement with data from previous reports (14,35). Thus, these results suggest that MC159 antagonized NEMO polyubiquitination, likely by interacting with NEMO, and warranted further study into how MC159 prevented NEMO polyubiquitination.…”
supporting
confidence: 90%
“…MC159 does not inhibit RIP1-NEMO interactions. Our and data and those reported previously by others showed that MC159 coimmunoprecipitates with RIP1 (39,40) and NEMO (14,35). IKK must interact with RIP1 for NF-B activation (23).…”
supporting
confidence: 89%
See 3 more Smart Citations